2022
DOI: 10.3390/land11091539
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Radionuclides in the System: Water, Irrigated Soils, and Agricultural Plants of the Crimea Region

Abstract: In the frame of the radioecological monitoring after the Chernobyl nuclear power plant accident, the features of migration and distribution of artificial radionuclides in the North Crimean Canal (NCC) irrigation system were studied. Standard methods of radiochemical analyzes and modern radiospectrometric equipment were used. It was determined that the irrigation system of the NCC retains 43–59% 90Sr, 59–60% 239+240Pu, and 66–70% 137Cs of the concentration radionuclides entering to irrigated fields with the Dni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The main source of radioactive strontium is nuclear fission (Bogdanovich et al, 1998 ; Mirzoeva et al, 2022 ; Tsukada et al, 2023 ). Out of Sr radioisotopes produced through nuclear fission, 90 Sr is particularly dangerous to humans, with its amount reaching up to 5.8% (Ageeva et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main source of radioactive strontium is nuclear fission (Bogdanovich et al, 1998 ; Mirzoeva et al, 2022 ; Tsukada et al, 2023 ). Out of Sr radioisotopes produced through nuclear fission, 90 Sr is particularly dangerous to humans, with its amount reaching up to 5.8% (Ageeva et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the contamination of fiber flax grown on lands contaminated with radionuclides in this zone showed that at a contamination density of Cs 137 of 20.5 Ci/km 2 , its content in the chaff reached 1539 Bq/kg, and in seeds it was 510 Bq/ kg [Kovalev et al, 2020]. The results of monitoring of radioactive contamination of agricultural crops under irrigation conditions in the steppe zone of Crimea indicate that at present the levels of radionuclide activity concentration in cultivated crops do not exceed the temporarily permissible level [Mirzoeva et al, 2022].…”
Section: Introductionmentioning
confidence: 99%